Coexistence of Behçet's Disease and Ankylosing Spondylitis: A Case Report - Hikmet Koçyiğit,; Yasemin Turan,; Korhan Bayram,; Alev Gurgan,; Hülya Deveci,; Anıl Güvenç, (Archives of Rheumatology, 2010)
Although overlap syndrome is frequently encountered in rheumatology practice, only a few cases of coexisting Behçet's disease and ankylosing spondylitis have been reported in the literature. Thus, in this article, we aimed to present a 55-year-old male patient with coexisting Behçet's disease and ankylosing spondylitis who had HLA-B5 positivity, HLA-B27 negativity, and oral and genital lesions. (Turk J Rheumatol 2010; 25: 217-20)